Studies on Ottoman transformation - Ortaylı, İlber 1947- (Analecta Isisiana: Ottoman and Turkish Studies, 2010)
A collection of essays on Ottoman political history, ranging from the eighteenth through to the twentieth centuries as the Empire went through a series of transformations